Teachers' Perceptions of Artificial Intelligence (AI) Integration in Learning at SMKN 3 Surakarta - Danila Rifki Saputri; Tutik Susilowati (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2026)
AbstrakPenelitian ini bertujuan untuk mengetahui: (1) sikap guru SMK N 3 Surakarta terhadap penggunaan Artificial Intelligence (AI) dalam pembelajaran, dan (2) persepsi guru terhadap integrasi AI dalam proses belajar mengajar.Penelitian ini dilatarbelakangi oleh masih terbatasnya kajian yang secara spesifik membahas persepsi guru sekolah menengah kejuruan terhadap penggunaan AI dalam konteks pembelajaran. Menggunakan pendekatan mixed methods dengan desain explanatory sequential, data kuantitatif diperoleh melalui angket kepada 73 guru, sedangkan data kualitatif dikumpulkan melalui wawancara terstruktur, observasi langsung, dan dokumentasi untuk memperdalam hasil kuantitatif. Hasil menunjukkan bahwa sebagian besar guru bersikap positif terhadap penggunaan AI karena mendukung efisiensi dan personalisasi pembelajaran. Namun, kekhawatiran juga muncul terkait pemahaman teknologi, keterbatasan pelatihan, dan potensi tergantikannya peran guru. AI dipandang sebagai alat bantu, bukan pengganti guru. Penelitian ini merekomendasikan pelatihan berkelanjutan, penguatan literasi AI, serta kebijakan implementasi yang bertahap dan etis untuk mendukung pemanfaatan AI secara optimal di sekolah kejuruan. Penelitian ini memberikan kontribusi berupa gambaran empiris mengenai kesiapan guru SMK dalam mengadopsi AI sebagai bagian dari transformasi digital pendidikan.Kata kunci : Artificial Intelligence; persepsi guru; sikap guru; pembelajaran digital AbstractThis study aimed to investigate: (1) the attitudes of teachers at SMK Negeri 3 Surakarta toward the use of Artificial Intelligence (AI) in learning, and (2) teachers' perceptions regarding the integration of AI in the teaching and learning process. The study was motivated by the limited body of research specifically addressing vocational secondary school teachers' perceptions of AI use in educational contexts. A mixed-methods approach with an explanatory sequential design was employed; quantitative data were collected through questionnaires administered to 73 teachers, while qualitative data were gathered through structured interviews, direct classroom observations, and document analysis to extend and deepen the quantitative findings. Results indicated that the majority of teachers held positive attitudes toward AI, perceiving it as a tool that enhances learning efficiency and enables personalized instruction. Nonetheless, concerns were expressed regarding students' potential over-reliance on technology, diminished direct teacher-student interaction, and data privacy risks. Teachers consistently framed AI as a pedagogical aid rather than a substitute for the teaching profession. The study recommends sustained AI literacy training, the establishment of evidence-based and ethically grounded implementation policies, and the development of institutional support structures to facilitate the responsible and optimal integration of AI in vocational school settings. These findings contribute an empirical account of vocational school teachers' readiness to adopt AI as a component of broader digital transformation in education.Keywords: Artificial Intelligence; teacher perception; teacher attitude; digital learning; vocational school